LEGAL REGULATION OF THE USE OF UNMANNED AIRCRAFT IN CIVIL AVIATION OF UKRAINE - Slobodska, Iryna; Yukhymovych, Maryna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: research into the legal regulation of the use of unmanned aerial vehicles in the civil aviation of Ukraine - technical requirements, safety standards, the creation of special flight zones, qualification requirements for remote flights and other issues are of practical importance for increasing the effectiveness of cooperation between Ukraine and the EU in aviation industry and creation of a modern legal framework. Research methods: this scientific work was written by the authors using generally recognized methods of scientific knowledge, such as formal, comparative-legal, analytical, system-structural and other methods. Results: the legal regulation of the use of unmanned aerial vehicles in the civil aviation of the European Union and Ukraine was investigated, existing gaps in the current legislation of Ukraine were pointed out, the author’s recommendations were given to overcome such shortcomings by reforming the current national legislation. Discussion: the discussion in this study is devoted to the peculiarities of the legal regulation of the use of unmanned aerial vehicles in the civil aviation of the European Union and Ukraine, as well as identifying the pros and cons of the new draft law, dedicated to the regulation of the specified issue. According to the provisions of the Convention on International Civil Aviation of 1944 (Chicago Convention), a type of aircraft is an unmanned aircraft, the flight of which in the sovereign airspace is possible only with the permission of a state party to the convention in areas open to civil aircraft flights. This is actually the only provision of the universally recognized Chicago Convention dedicated specifically to unmanned aerial vehicles. As the number of unmanned aerial vehicles began to increase, ICAO developed a number of standards in this area. Gradually, ICAO member states, within the framework of domestic legislation, began to develop their own legal models in order to eliminate legal "gaps" regarding the use of unmanned aerial vehicles. Considering Ukraine’s course towards European integration, the signed association agreements with the European Union and the gradual creation of a common aviation space, our state needs not only to create new legal norms regarding the use of unmanned aerial vehicles, but also to review the ones that have already been created. That is why the issue of legal regulation of the use of unmanned aerial vehicles in the civil aviation of Ukraine is still relevant today. Although drones have entered our lives quite recently and the field of drones continues to form and take shape, the possible potential threats from their misuse are obvious. Therefore, the introduction of legislative regulation of the use of drones in Ukraine is an urgent issue that requires an urgent solution, taking into account the experience of the leading countries of the world.